Analisis Strategi Pemasaran Dalam Meningkatkan Penjualan Jasa Pada Pabrik MC Washing - Nurzanah, Rike; Rinaldi, Aris (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
Marketing strategy plays an important role in increasing competitiveness and business growth, especially in the denim washing industry. This study aims to analyze the marketing strategy implemented by MC Washing to increase its service sales. This study uses a qualitative approach with data collection methods through observation, interviews, and documentation. The data were analyzed using SWOT analysis and the 7P marketing mix. The results showed that MC Washing has implemented a strategy based on service quality and customer satisfaction. The company relies heavily on word-of-mouth strategies and offers pick-up and drop-off services to increase customer convenience. However, challenges remain, such as limited warehouse storage capacity and a lack of digital marketing. This study recommends enhancing digital promotion, modernizing technology, and expanding capacity to increase competitiveness.